Proceedings of the 5th Conference on Innovations in Theoretical Computer Science 2014
DOI: 10.1145/2554797.2554800
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenography

Abstract: We consider the following cryptographic secret leaking problem. A group of players communicate with the goal of learning (and perhaps revealing) a secret held initially by one of them. Their conversation is monitored by a computationally unlimited eavesdropper, who wants to learn the identity of the secret-holder. Despite the unavailability of key, some protection can be provided to the identity of the secretholder. We call the study of such communication problems, either from the group's or the eavesdropper's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Brody et al [4] studied the following cryptogenographic problem. We flip a coin, and tell the result to one out of n people.…”
Section: The Original Cryptogenography Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Brody et al [4] studied the following cryptogenographic problem. We flip a coin, and tell the result to one out of n people.…”
Section: The Original Cryptogenography Problemmentioning
confidence: 99%
“…We assume that both Frank and Eve make their guesses to maximise the probability that they win, rather than maximise the probability of being correct. 6 For n = 2, Brody et al [4] showed that the group would win with probability 1 3 but no protocol can ensure winning with probability above 3 8 . Doerr and Künnemann [12] later improved this upper bound to 0.3672 and the lower bound to 0.3384.…”
Section: The Original Cryptogenography Problemmentioning
confidence: 99%
See 3 more Smart Citations